Clinical features, diagnosis, and outcomes of rhino-orbito-cerebral mucormycosis: A retrospective analysis - Akram Abdollahi (Current Medical Mycology, 2016)
Background and Purpose: Rhino-orbito-cerebral mucormycosis (ROCM) is a rare disease with acute and fulminant manifestation. This infection is associated with high morbidity and mortality rates. Herein, we reviewed the manifestations, underlying conditions, medical treatments, and surgical interventions in ROCM patients admitted to a tertiary referral center in northern Iran over a seven-year period. Materials and Methods: In a retrospective analysis, 15 cases of ROCM were identified from 2007 to 2013 in Bu Ali Sina Hospital, Sari, Iran. All the ROCM cases were clinically diagnosed and confirmed by histopathological and/or mycological examination. The relevant demographic data, clinical, ophthalmic, and neurologic manifestations, underlying conditions, medical treatments, and surgical interventions were recorded and analyzed. Results: The mean age of the patients was 54±11 years (age range: 28–70 years); 26.7% of the patients were male and 73.3% female (male: female ratio of 1: 2.7). Uncontrolled diabetes was noted in at least 86.7% (13/15) of the cases. The maxillary sinuses were the most frequently involved sites (66.7% of the cases) followed by the ethmoid sinus. Amphotericin B in combination with surgical debridement was used in the treatment of 80% of the cases. Furthermore,73.3% of the patients who were diagnosed early and underwent medical and extensive surgical debridement of the infected tissues survived. Conclusion: Uncontrolled diabetes mellitus is considered to be the main predisposing factor for ROCM. To prevent and reduce mortality rate of this acute disease, early diagnosis based on clinical findings and biopsy is recommended.